Reaching Mobile Populations in Mass Drug Administration for Neglected Tropical Diseases: Evidence from Mali and Broader Implications for Africa - Sangare, Moussa (Université d'Ottawa | University of Ottawa, 2026)
Neglected Tropical Diseases (NTDs) affect over a billion people globally, with mass drug administration (MDA) being one of the cornerstone strategies for control and elimination. However, mobile populations such as nomads, internally displaced persons (IDPs), migrants, and seasonal workers are frequently missed during MDA campaigns. This gap threatens progress toward the global targets for NTDs outlined in the WHO Roadmap 2021–2030, particularly in endemic regions like Mali and across Africa. Understanding the barriers to MDA participation among these groups is essential for designing equitable and effective interventions. Three complementary studies were conducted to explore MDA access among mobile populations. A cross-sectional study in Mali (2020–2021) used structured questionnaires and multivariable regression to identify factors associated with non-participation in schistosomiasis MDA. A qualitative study in Mali (2023) used in-depth interviews and focus group discussions to explore reasons for never being treated during MDA among mobile groups. Finally, a scoping review (2024/2025) followed PRISMA-ScR guidelines, synthesized evidence from 20 studies across Africa on mobility-related barriers to MDA. The following results present the main findings of our research. MDA coverage among mobile populations was consistently below the recommended 75% threshold. In Mali, only 40.8% of internally displaced people (IDPs) and 3.62% of migrants participated in the last MDA round. Key barriers included: lack of information (64.5%), geographic inaccessibility, mobility patterns (e.g., transhumance, seasonal work), low income and occupations such as mining, fear of side effects and rumors, and inflexible campaign schedules. Our findings also revealed that males, those facing physical or geographic barriers, and nomadic groups were significantly more likely to miss MDA. The scoping review highlighted additional systemic issues such as limited cross-border coordination and insufficient community engagement. Identified promising strategies included mobility-informed microplanning, flexible delivery models, and integrated health services. Mobile populations are systematically excluded from MDA programs, undermining efforts to eliminate NTDs. Addressing these disparities requires context-specific, adaptive, and participatory approaches. To ensure no one is left behind, MDA programs must move beyond one-size-fits-all models. Tailored strategies that account for mobility patterns, livelihood contexts, and local barriers are urgently needed.
Keywords: Schistosomiasis; Mobile populations; Mass drug administration; Never treated; Risk factors; Mali